2018
DOI: 10.9734/acri/2018/41831
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Transfusion-Transmissible Infections among Volunteer Blood Donors in Rural Area of Eastern Democratic Republic of the Congo (D.R.C)

Abstract: Background: Transfusion safety investigations in sub-Saharan Africa are sparse, often limited to local initiatives. The provision of transfusion products must comply with the rules of good transfusion practice. This study aimed to evaluate transfusion practices in a rural area in the Eastern Democratic Republic of the Congo and identifying the main Infectious Transfusion Infections. Methodology: This was a retrospective study carried out from January to December 2017 and including 961 volunteer blood donors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In Uganda and China, urban HCWs were more likely to be screened [ 7 , 20 ] possibly because of the greater availability of screening kits. The low screening and vaccination rates we observed could be due to the regular disruption of the health system in the eastern DRC due to socio-political instabilities (including war) [ 9 ]. Despite these issues, we found that HCWs who knew they were at high risk of HBV infection, understood its mode of transmission, and the benefit of vaccination were those most likely to have been screened for HBV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda and China, urban HCWs were more likely to be screened [ 7 , 20 ] possibly because of the greater availability of screening kits. The low screening and vaccination rates we observed could be due to the regular disruption of the health system in the eastern DRC due to socio-political instabilities (including war) [ 9 ]. Despite these issues, we found that HCWs who knew they were at high risk of HBV infection, understood its mode of transmission, and the benefit of vaccination were those most likely to have been screened for HBV.…”
Section: Discussionmentioning
confidence: 99%
“…In the Democratic Republic of the Congo (DRC), health and education systems have been disrupted by multiple socio-political instabilities. Although its prevalence of HBV infection is among the highest in the world [ 9 ], the overall risk of these infections to HCWs is largely unknown [ 10 ]. A survey conducted in Bukavu, a town in South Kivu DRC, revealed that HCWs had a low level of knowledge about HBV and only 3.8% of vaccinated HCWs had received the complete vaccination schedule of three vaccine doses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in transfusion safety, transfusion-related infections remain a concern [3,4]. Indeed, according to the World Health Organization (WHO) in 2018, the prevalence of transfusion-transmitted infections in donated blood would be much lower in high-income countries than in low-and middle-income countries below [5,6]. Indeed, the seroprevalence of HIV, hepatitis B, hepatitis C, and syphilis was 0.002%, 0.02%, 0.007%, and 0.02% in high-income countries, respectively; and 0.70% 2.81% 1.00% 0.90% in low-income countries [5].…”
Section: Introductionmentioning
confidence: 99%